FIDUCIARY OBLIGATIONS OF THE BOARD OF DIRECTORS IN MANAGING COMPANY SHARES: A CORPORATE LAW AND CAPITAL MARKET PERSPECTIVE - Lenny Mutiara Ambarita (CV. RADJA PUBLIKA, 2025)
Fiduciary duty is a fundamental principle in modern corporate law that requires directors to act in good faith, with due care, and prioritize the interests of the company over personal interests. In the Indonesian context, this obligation has been regulated normatively through Law Number 40 of 2007 concerning Limited Liability Companies and Law Number 8 of 1995 concerning Capital Markets. However, the implementation of fiduciary duty still faces various obstacles, both in terms of legal norms and judicial and capital market practices. This study uses a normative legal method with a statutory, conceptual, and comparative approach. The data used are primary legal materials such as laws, Financial Services Authority regulations, and court decisions, as well as secondary legal materials in the form of literature, scientific journals, and previous research results. The analysis was conducted qualitatively normatively through legal interpretation and construction. The results of the study indicate that although fiduciary duty has a legal basis, its implementation remains weak. From a corporate law perspective, the standards for implementing the duty of care and duty of loyalty remain unclear, making it difficult for minority shareholders to hold directors accountable. In judicial practice, the application of fiduciary duty is often inconsistent due to varying standards of proof. Meanwhile, from a capital market perspective, violations such as insider trading and conflicts of interest involving nominee directors remain rampant, which cannot be fully controlled by the Financial Services Authority (OJK)'s oversight mechanisms.